2003
DOI: 10.1002/uog.211
|View full text |Cite
|
Sign up to set email alerts
|

Fetal blood sampling in twin pregnancies

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
(25 reference statements)
0
3
1
Order By: Relevance
“…The data from previous studies and ours are summarized in Table 3. Compared with previous studies (Cox et al , 1987; Antsaklis et al , 2003), fetal loss within 2 weeks of the procedure in our study occurred at the lowest rate (1.1%), whereas the success rate of fetal blood sampling was comparable. However, several aspects of the techniques do not allow proper comparison of the results.…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…The data from previous studies and ours are summarized in Table 3. Compared with previous studies (Cox et al , 1987; Antsaklis et al , 2003), fetal loss within 2 weeks of the procedure in our study occurred at the lowest rate (1.1%), whereas the success rate of fetal blood sampling was comparable. However, several aspects of the techniques do not allow proper comparison of the results.…”
Section: Discussioncontrasting
confidence: 71%
“…The time frames of database collection, especially in the study by Cox et al (1987), could have affected the quality of the ultrasound imaging. In the largest study reported by Antsaklis et al (2003), the fetal loss rate was 8.2% but the series also included fetal blood samplings via fetoscopy, which is a more invasive technique of fetal blood sampling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mortality rates are high, reaching 80 to 100% in untreated disorders. There is also high occurrence of miscarriage, premature rupture of membranes, preterm delivery and spontaneous death of one or both siblings [79].…”
Section: Severity Stagingmentioning
confidence: 99%